Islam hadhari : himpunan isu kontemporari - A. Monir Yaacob (Abdul Monir Yaacob); Norhanizah Ismail (Kuala Lumpur : Institut Kefahaman Islam Malaysia, 2005)
Issues on religious life, women, science, and politics in Malaysia from Islamic perspectives; collection of articles previously published in Utusan Malaysia newspaper during 2001 to 2003.
In Malay.